Factors That Influence the Visits of The Fourth Trimester (K4) For Pregnancy at the Soibada Health Center, Soibada Administrative Post, Manatuto Municipality, Timor-Leste, 2023 - Carvalho de Araujo, Eugenia; Costa Monteiro, Ermelinda da; Jose Soares Tilman, Etelvina; Pereira, Natalia; Barreto Amaral, Meriana; Costa Soares, Lorena da (Jurnal KESANS : Kesehatan dan Sains, 2024)
Introduction: The pregnancy is a natural process that occurs in women with reproductive age; for the pregnant to occur, it requires a process that meets the egg cell and spermatozoon when having sexual intercourse during ovulation. According to the Timor Leste Health Demographic Survey 2016, the maternal mortality rate is 218/100,000 live births. The Ministry of Health data showed that K1 and K4 visits reached 80 90%. The report from the Ministry of Health in 2022 revealed that the initial pregnant mother visits (K1) in the center reached 39,608 (79%), and K4 visits reached 26,567 (53%). The Soibada Health Center report in 2020 showed that the initial pregnant mother visits (K1) total of 1931 (71%) and K4 visits with a total of 1415 (52%). Objective: To determine the factors that influence the visits of the fourth trimester (K4) for pregnancy at the Soibada Health Center, Soibada Administrative Post, Manatuto Municipality, Timor Leste in the year 2023. Method: This research used quantitative analytical methods with a cross sectional approach. The population for this research is the pregnancy who visit the Soibada Health Center, Soibada Administrative Post. Result and Discussion: The respondents for this research were 88, with the following results: 36 (40.9%) had a primary education level, 46 (52.3%) were aged <20 or >35, 54 (61.4%) did not work together, 48 (54.5%) were Mult pregnancy, 47 (53.4%) had less knowledge, and there were 52 (59.1%) irregular visits to the clinic. Conclusion: Based on this research, we conclude that factors such as education level, age, occupation, parity, and knowledge influence irregular visits to the clinic. Therefore, we urge health personnel to pay more attention to these factors, especially in terms of consulting standards for women's health.